Leitura e ciberespaço: uma nova arquitetura de escrita e de sentidos - Baiocchi, Dileuza Niebielski (2014)
Abstract: The present research is inserted in the area of Language and Technology, and, as its central focus is the new kinds of social practices of reading and writing, making of blogs. It seeks to investigate the possibilities of reading and writing that emerge with TCIs, new communication media and virtual learning environments that are able to resize language practices in cyberculture and teaching in the school production of text. In that sense also search the blogs created in schools in order to awaken the taste for reading are meeting goals to form critical, participatory and assiduous readers. The study presupposes that it is desirable to promote into the classroom the language experiences mediated by digital media students already experience in their daily. The research corpus is anchored in the literature as well as in cyberspace with interpretive analysis of discourse from the discourse theory of Ducrot. This essay reports the performed analysis from proposed activities in educational blogging in schools of public schools, in which TCIs are present. The research was motivated in order to determine how digital media were being adequately explored the practices of reading and writing in cyberspace and relevance to review the nature of language, considering the changes that technology promotes. The theoretical research component initially discusses the importance of digital communication technologies, brief analysis of the network society, or the information society, the emergence of the knowledge era, the excess of information and contextualization of cyberspace and cyberculture. Then, it presents a general discussion on gender blog, environment explored in the analysis proposed in the study from the postulates of Ducrot. The results show that it is relevant to use the blog as a teaching tool and that the use of this feature is motivating for students and can lead to complex and creative productions